OPTIMIZATION OF COOPERATIVE MANAGEMENT CONTROL SYSTEM AISYIYAH MALANG - Mudrifah Mudrifah; Ihya`ul Ulum; Enny Suprapti (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2021)
The management control system is a system used to influence its members to implement strategies efficiently and effectively to achieve organizational goals. The purpose of this study was to find out how the implementation of management control systems in the Asisyiah Savings and Loans Cooperative Malang. The data analysis method used is descriptive. The results showed that the management control structure and management control process at KSP Asisyiah Malang were effective. This is evidenced by the implementation of a control structure which is divided into an organizational structure, a delegation of authority and responsibility, and a responsibility centre that covers all functions within the organizational structure. As well as the control process carried out starting from strategy formulation, budget preparation, implementation and measurement, as well as work evaluation which shows an improvement. Based on the results of the research, the servant can give suggestions that KSP Asisyiah needs to apply a division manager to separate the duties and responsibilities between the management and the manager. The addition of resources will improve performance for the progress of KSP Asisyiah Malang business. Work evaluation also needs to be compared between realization and what has been budgeted so that the results are more effective.